2010
DOI: 10.1155/2010/397865
|View full text |Cite
|
Sign up to set email alerts
|

Support Vector Machine for Behavior-Based Driver Identification System

Abstract: We present an intelligent driver identification system to handle vehicle theft based on modeling dynamic human behaviors. We propose to recognize illegitimate drivers through their driving behaviors. Since human driving behaviors belong to a dynamic biometrical feature which is complex and difficult to imitate compared with static features such as passwords and fingerprints, we find that this novel idea of utilizing human dynamic features for enhanced security application is more effective. In this paper, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Using real-world data, it is shown that only seven-second-long driving behavior signals and geolocation signals are used to identify drivers. Furthermore, the proposed algorithm achieves relatively high accuracy and also outperforms the previously proposed algorithms [6,7,9,10]. Lastly, for implementation purposes, real-world results associated with each operation of the proposed algorithm are shown step-by-step.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Using real-world data, it is shown that only seven-second-long driving behavior signals and geolocation signals are used to identify drivers. Furthermore, the proposed algorithm achieves relatively high accuracy and also outperforms the previously proposed algorithms [6,7,9,10]. Lastly, for implementation purposes, real-world results associated with each operation of the proposed algorithm are shown step-by-step.…”
Section: Introductionmentioning
confidence: 89%
“…More recently proposed algorithms use Support Vector Machine (SVM) and are more focused in using driving behavior signals as inputs [10,16]. In [16], signals from inertial sensors, namely, accelerometer and gyroscope, are processed in order to detect accelerating, braking, and wheel-turning events.…”
Section: Driver Identification In Real-world Situationsmentioning
confidence: 99%
See 3 more Smart Citations